Neuroprotective Effects and Mechanisms of Zhenlong Xingnao Capsule in In Vivo and In Vitro Models of Hypoxia - Wei, Xia; Zhu, Qingfen; Liu, Na; Xu, Lihua; Wei, Sheng; Fan, Zhiyun; Sun, Changhua; Zhao, Yan; Qiao, Mingqi; Wu, Jibiao; Hu, Defu; Wang, Yang; et al. (Frontiers in Pharmacology, 2019)
Zhenlong Xingnao Capsule (ZXC) is a Tibetan medicine used to treat ischemic stroke. In this study, we determined the in vitro and in vivo effects of ZXC on reactive oxygen species (ROS) in a mouse BV-2 microglial cell hypoxia-reoxygenation and rat middle cerebral artery occlusion infarction models. We aimed to clarify the role of ZXC in cerebral ischemia protection; reveal amino acid neurotransmitter changes in the frontal cortex after drug intervention; determine mRNA and protein expression changes in Bcl-2, Bax, caspase-3, P38, and nuclear factor (NF)-кB in the frontal cortex and changes in antioxidant indices in the brain; and elucidate the mechanisms underlying ZXC action. After hypoxia-reoxygenation, ROS levels were significantly increased in BV-2 cells, and their levels decreased after treatment with ZXC. ZXC had protective effects on ischemic/anoxic injury in vitro and in vivo by downregulating the expressions of caspase-3 and NF-кB mRNA during ischemia and reperfusion and that of p38 and caspase-3 during acute ischemia and reperfusion as well as the steady-state levels of excitatory amino acids/inhibitory amino acids and by improving the total antioxidant capacity and total superoxide dismutase activities during ischemia. These findings provide new molecular evidence for the mechanisms underlying ZXC action.